The Correlation Between Husband's Support and Self-Efficacy of Women in Choosing Long-Acting Reversible Contraceptives (LARC) - Shangrila Ayu Pelita; Rita Yulifah; Innas Tiara A (International Journal of Advanced Health Science and Technology, 2024)
Husband support is a strengthening factor in choosing long-term contraceptive methods. The problem is the husband's strong influence in determining the wife’s contraception. A wife becomes more confident in herself through the positive support of her husband. This study aims to find out the correlation between the husband's support with the self-efficacy of women of childbearing age in choosing LARC. The research design used is a correlational descriptive with a cross-sectional approach. The population of LARC acceptor PUS was 42 people, sampling using proportional random sampling with 38 respondents who met the inclusion criteria. The research instrument uses husband support query sheets and self-efficacy questionnaires that have been tested for validity and reliability. The Spearman correlation test shows a correlation coefficient of 0.564 which is strongly correlated. As well as the significance level of 0.000 < 0.05, which means there is a correlation between the husband's support and PUS self-efficacy in choosing LARC. The promotional action to increase the confidence of the use of LARC is to increase the provision of information on LARC contraception.